2022
DOI: 10.1016/j.molmet.2022.101436
|View full text |Cite
|
Sign up to set email alerts
|

NFE2L1-mediated proteasome function protects from ferroptosis

Abstract: Objective Ferroptosis continues to emerge as a novel modality of cell death with important therapeutic implications for a variety of diseases, most notably cancer and degenerative diseases. While susceptibility, initiation, and execution of ferroptosis have been linked to reprogramming of cellular lipid metabolism, imbalances in iron-redox homeostasis, and aberrant mitochondrial respiration, the detailed mechanisms of ferroptosis are still insufficiently well understood. Methods and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…In addition, lipid peroxidase inhibitors (such as vitamin E) can not only inhibit LOX activity, but also have weak chemical bonds to facilitate the transport of hydrogen atoms, which protect cells from ferroptosis and oxidative damage [ 64 ]. Recent studies have confirmed that transcription factor nuclear factor erythroid-2, like-1 (NFE2L1), maintains proteasome function, which reveals a new mechanism of anti-ferroptosis [ 65 ].…”
Section: Mechanism Of Ferroptosis and Ferritinophagymentioning
confidence: 99%
“…In addition, lipid peroxidase inhibitors (such as vitamin E) can not only inhibit LOX activity, but also have weak chemical bonds to facilitate the transport of hydrogen atoms, which protect cells from ferroptosis and oxidative damage [ 64 ]. Recent studies have confirmed that transcription factor nuclear factor erythroid-2, like-1 (NFE2L1), maintains proteasome function, which reveals a new mechanism of anti-ferroptosis [ 65 ].…”
Section: Mechanism Of Ferroptosis and Ferritinophagymentioning
confidence: 99%
“…However, p53 can also inhibit ferroptosis by the inhibition of dipeptidyl peptidase 4 or through the enhancement of cyclin dependent kinase inhibitor 1 A ( 61 ). It has been reported that proteasome function is often inhibited during ferroptosis ( 62 ). Numerous metabolic and degradation pathways, including the ubiquitin-proteasome system, orchestrate the complex ferroptotic response through the regulation of iron accumulation or lipid peroxidation ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Food intake and body weight were determined weekly and after the end of the adaptation period, whole-body oxygen consumption as well as CL-316,243-induced adrenergic (1 mg/kg of body weight) response was measured using indirect calorimetry. Resting and CL- 316,243-induced oxygen consumption was indirectly measured using Sable Systems Promethion Indirect Calorimetry System (Kotschi et al, 2022). For animals with IF1 overexpression in BAT (see protocol below), 3 weeks after surgery, resting oxygen consumption (VO 2 ) and carbon dioxide production (VCO 2 ) were monitored in metabolic cages (Columbus Instruments, Columbus, OH, USA) at 22 °C (Brunetta et al, 2020).…”
Section: Methodsmentioning
confidence: 99%